Ramona and her mother - Cleary, Beverly; Tiegreen, Alan (New York : Morrow, 1979)
Ramona at 7 1/2 sometimes feels discriminated against by being the youngest in the family.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
School Library Journal.
5.3
3-6
Keywords: Family life -- Fiction; Mothers and daughters -- Fiction; Family life -- Fiction; Mother-daughter relationship -- Fiction; Family life -- Fiction; Mothers and daughters -- Fiction